CALCULATION OF COST OF COST OF PRODUCTION USING THE FULL COSTING METHOD FOR CANTING AMEH UMKM IN NAGARI KUMANIS - Guspendri, Nasfizar; Putri, Fanny Rizma; Rahmadani, Amelia (UIN MAHMUD YUNUS BATUSANGKAR, 2025)
This study aims to determine how to calculate the cost of goods produced using the full costing method. The method used is qualitative with a descriptive approach. The data collection technique used is the documentation technique by collecting information in the form of production costs at UMKM Canting Ameh Nagari Kumanis. The results showed that there were differences in the calculation of the cost of goods produced by UMKM Canting Ameh Nagari Kumanis with the calculation of the cost of goods produced using the full costing method. This is because the calculation of the cost of goods produced by UMKM Canting Ameh does not take into account all costs incurred. The cost of goods produced using the full costing method is higher because the calculation of production costs is more detailed about the costs incurred. By using the full costing method, UMKM actors no longer need to pay for and take the profit earned for depreciation costs.